2018
DOI: 10.22201/fesi.20071523e.2018.1.447
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of conditioned taste aversion on sucrose and stevia intake / Efectos diferenciales del condicionamiento aversivo a sabores sobre la ingesta de sacarosa y estevia

Abstract: The association between a food stimulus and a feeling of discomfort produces a food aversion; this procedure is called aversive taste conditioning (ATC). Since there is no clear evidence about the effects of this procedure on the consumption of sweeteners, the purpose of this study was to examine the effectiveness of ATC to decrease the consumption of two natural sweeteners. Thirty Wistar rats were divided into three groups. In phase 1 all groups were exposed to free food access and each group to a different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The cafeteria diet is characterized by a high calorie diet that contains highly palatable foods, such as chocolate, peanuts and biscuits. It is also considered a high-fat diet, as it contains a large amount of saturated fats, besides containing large amounts of sugars, which please rodents' taste (Martinez-Moreno et al, 2017;Padilla et al, 2019). The present study showed that a standardized cafeteria diet administered from birth to adulthood can promote a condition of hepatic steatosis in animals, with micro and macrovacuoles, accumulation of lipids in the liver and redox imbalance of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…The cafeteria diet is characterized by a high calorie diet that contains highly palatable foods, such as chocolate, peanuts and biscuits. It is also considered a high-fat diet, as it contains a large amount of saturated fats, besides containing large amounts of sugars, which please rodents' taste (Martinez-Moreno et al, 2017;Padilla et al, 2019). The present study showed that a standardized cafeteria diet administered from birth to adulthood can promote a condition of hepatic steatosis in animals, with micro and macrovacuoles, accumulation of lipids in the liver and redox imbalance of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…Los EC que se han utilizado con más frecuencia en investigaciones con modelos murinos son soluciones endulzadas (Ackroff et al, 1993;Anderson et al, 2006;Martínez-Moreno et al, 2018;Miranda et al, 2023;Misanin et al, 2002), aunque los sabores de las proteínas parecen ser más efectivos que los carbohidratos en el condicionamiento aversivo (Sclafani & Ackroff, 2020). Sin embargo, en otros modelos animales el estudio del CAS se ha extendido a diferentes alimentos en presentación sólida, entre los que se han incluido, principalmente debido a sus características organolépticas y aporte calórico o por su toxicidad, pasas, cacahuates, maíz molido, huevos de codorniz, gusanos blancos, harina, mezcla de avena y azúcar glas en ratas, hierba carmín en caballos, varias especies de gramíneas en ovejas y hojas de Mascagnia rigida en cabras (Barbosa et al, 2008;Gentle et al, 2006;Ginane & Dumont, 2006;Pfister et al, 2002).…”
Section: Introductionunclassified